ANALISIS FAKTOR INTERNAL DAN FAKTOR EKSTERNAL USAHATANI TANAMAN KOPI (Coffea Arabika) DI DESA SUKA KABUPATEN KARO - Ate Tarigan, Ruth Riah; Setyanigrum, Sri; Hafiz, Muhammad (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2023, 2023)
The coffee plant is an important plantation commodity to improve the economy of the people living in Karo Regency. The type of coffee developed by the Karo people is Arabica coffee. The aim of the study was to analyze the internal factors and external factors that influence the strategy for developing coffee farming (Coffea arabika) in Suka Village, Karo Regency. The data analysis method used in explaining problem identification is descriptive analysis. The results of the study are the Internal Factors of strength, namely natural resources, coffee taste, human resources, coffee harvest time, farmer groups, and transportation access. The dominant force affecting the development of coffee farming in the research area is human resources. Internal factors of weakness are coffee plant seeds, coffee marketing, coffee farmer partnerships, coffee processing, and coffee plant maintenance. The most dominant weakness is the maintenance of coffee plants. Opportunity external factors are: location of coffee cultivation, demand for coffee, profit of coffee farming and quality of coffee beans. The most dominant opportunity is the demand for coffee. External threat factors are: coffee farming competition, climate change, coffee pests and diseases and coffee prices. The most dominant threat is competition in coffee farming.